Exploring untapped potential of cashew apple for masses - Balasubramanian, D; Saroj, P L (Indian Horticulture, 2019)
The commercial destination of cashew crop is almost exclusively restricted to the processing of cashew nuts which is currently the major export earning commodity. Cashew is mainly grown for its nut, but cashew apple which is a swollen peduncle to which the nut is adhering to and called as pseudo or false fruit, is not utilized to the fullest extent. Nutritive and qualitative characters of the apple have clearly indicated its superior position compared to other fruits. The yield of cashew apple is 8-10 times that of cashew nut and annual harvests of cashew apple in India exceeds 60 lakh tonnes, representing an opportunity for processing and make cashew industry a highly profitable one. Hardly 10- 15% of the total production in our country is either consumed naturally or processed industrially into beverages. The high degree of cashew apple waste is primarily due to rapid degradation and lack of convenient harvesting procedures. Cashew apple is utilized to prepare a variety of traditional products such as jam, compotes, syrups, dried fruit, fresh and carbonated fruit juices, wine and alcohol, says Dr P L Saroj, Director, Directorate of Cashew Research, Puttur, Karnataka.